DESAIN KURIKULUM PENDIDIKAN ISLAM BERBASIS TEKNOLOGI (STRATEGI INTEGRASI NILAI MORAL DAN KOMPETENSI) - Hoerul Umam; Wulan Setyaningrum; Siti Fathonah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Islamic education in the contemporary era faces significant challenges in aligning religious traditions with the rapid development of digital technology. This study aims to analyze the design of an Islamic education curriculum that integrates moral values ​​with technological competencies to shape a superior generation. The research method used is a qualitative approach with library research, where data is collected from various scientific literature related to digital transformation in Islamic educational institutions. The results show that effective curriculum integration must encompass three main aspects: 1) a pedagogical aspect that emphasizes the internalization of the values ​​of honesty, responsibility, and cooperation in digital activities; 2) a content aspect that aligns the teachings of the Qur'an and Hadith with the needs of 21st-century skills; and 3) a technological aspect through the use of online learning platforms, the digitization of teaching materials, and the use of interactive media. Curriculum strengthening strategies are implemented through increasing the digital capacity of educators, the use of adaptive technology for personalized learning, and a project-based assessment system. This study concludes that the synergy between technological competency and Islamic ethical foundations is the main key